Problems and potential of mineral magnetic measurements as a soil particle size proxy - Booth, Colin A.; Fullen, Michael A.; Walden, John; Worsley, Annie T.; Marcinkonis, Saulius; Coker, Akinwale O. (Journal of Environmental Engineering and Landscape Management, 2008)
The use of mineral magnetic concentration parameters (χLF, χARM and SIRM) as a potential particle size proxy for soil samples collected from the Isle of Man (British Isles) is explored as an alternative means of normalizing particle size effects. Comparison of soil‐related analytical data by correlation analyses between each magnetic parameter and individual particle size classes (i.e. sand, silt and clay), more discrete intervals within classes (e.g. fine sand or medium silt) and cumulative size fractions (e.g. clay + fine silt) are reported. Both χLF and χARMparameters reveal significant (p